" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
[ 9^(1/3) x 27^(1/2) ] / [9^(1/6) x 3^(2/3)]
= (3^(2/3) x 3^(3/2) / ( 3^(1/3) x 3(2/3)
= (3)^(3/2 - 1/3)
= 3^(7/6)
.
2)
3^(7x+6) = (1/27)^(-4x+3)
3^(7x+6) = (3)^-3(-4x+3)
7x + 6 = -3(-4x+3)
7x - 6 = -12x - 9
7x+12x = -9+ 6
19x = -3
x = -3/19
.
3)
9'log x + 9'log x^2 + 9'log x^3 + 9'log x^4 = 5
9'log (x)^(1+2+3+4) = 9'log 9^5
x^10 = 9^5
x ^10 = 3^10
x = 3
.
4)
3'log 3^(x + 6) = 3 - x,
3^(3-x) = 3^(x+6)
3-x = x+6
-x-x = 6-3
-2x= 3
x = - 3/2